Pemanfaatan TOGAF untuk Merevolusi Arsitektur Enterprise pada Industri Padat Karya - Juan Richard Harmel; Wella Wella (Universitas Islam Raden Rahmat, Malang, 2024)
Labor-intensive industries face challenges in optimizing information systems and technology. Disconnected business processes cause scattered data and poor application integration. A structured approach is required to design an enterprise architecture aligning business and IT strategies. This study explores TOGAF implementation in a labor-intensive business in Jakarta, focusing on creating a more efficient architecture. The research provides design recommendations, including human resource management portal enhancements. Using TOGAF and UML, the study successfully created an enterprise architecture addressing business, application, data, and technology needs, improving departmental integration, overall business performance, and service delivery. It effectively bridges IT and business strategies.